P051 Phase 1a Safety and Pharmacokinetic Effects of GB004, a Novel Prolyl Hydroxylase Inhibitor and Potential Therapy for Inflammatory Bowel Disease. (December 2019) - Levesque, Barrett; Flynn, Michael; Peters, Kevin; Buch, Akshay
Abstract : BACKGROUND: GB004 is a small molecule prolyl hydroxylase inhibitor (PHDi) that stabilizes hypoxia inducible factors (HIF-α), key transcription factors involved in the adaptive and protective cellular responses at the intersection of hypoxia and inflammation. GB004 is being developed as a therapy for inflammatory bowel disease (IBD). For diseases such as IBD, an ideal profile for a PHDi is a molecule that has a gut targeted PK profile and preferentially activates tissue specific protective mechanisms to a greater extent than other pathways where HIF transcription factors have a role (e.g., erythropoietin (EPO) production). GB004 was selected to meet this profile, and consistent with it, orally administered GB004 in animal models of colitis demonstrated a significant reduction in disease activity, an improvement in histology, greater exposure in GI tissue relative to plasma, and no increase in systemic EPO or hematocrit. This single ascending dose (SAD) study is the first-in-human study to evaluate the safety, tolerability, and PK of GB004 in healthy subjects. This study also determined the pharmacodynamic (PD) effects of GB004 on plasma EPO and vascular endothelial growth factor (VEGF). METHODS: This was a randomized, double-blind, placebo-controlled, single-ascending dose, Phase 1a study conducted at a single site in Canada. Single oral solution doses were investigated in 5 sequential cohorts (20, 60, 120, and 240 mg in 50 ml solution, and 240 mg in 100 ml solution), consisting of 2 placebo and 6 GB004 male subjects per cohort. PK and safety were evaluated through follow-up on day 8. EPO and VEGF levels were collected at baseline, 4, 8, and 12 hours post dose. RESULTS: 40 subjects were randomized. The mean age and BMI were 36.2 yrs and 25.61 kg/m2, respectively. All subjects completed the study. GB004 was rapidly absorbed with a median Tmax of 0.5 hour for all doses. Cmax of GB004 increased in a dose proportional manner while AUC of GB004 increased slightly larger than dose proportional. GB004 was rapidly eliminated from systemic circulation. No dose related changes were observed in plasma EPO or VEGF at any dose level. There were no adverse events (AEs) leading to discontinuation, serious adverse events (SAEs) or deaths. The incidence of AEs in the 30 GB004-treated subjects was 46.7% vs 50.0% in the 10 placebo-treated subjects. AEs with an incidence of >=10% in GB004-treated subjects and higher than in placebo were: nausea (20.0% GB004 vs 0% placebo), vomiting (13.3% vs 0%), feeling cold (13.3% vs 10.0%), and somnolence (10.0% vs 0%). All AEs reported in GB004-treated subjects were mild, and the incidence of AEs for GB004 240 mg in 100 ml was lower than 240 mg or 120 mg in 50 ml. CONCLUSION(S): This study demonstrated that single doses of GB004 solution were generally well tolerated, with no effects observed on serum EPO or VEGF levels, consistent with the intended PK profile and animal model data. Clinical studies of GB004 are ongoing in patients with ulcerative colitis to explore PK and PD both systemically and within colonic tissue (NCT03860896). A tablet formulation is being developed.